Theoretical kinetics of hydrogen abstraction and hydroperoxyl addition reactions of 3-hexene by hydroperoxyl radicals. (1st October 2020) - Jin, Wu; Tang, Chaowei; Yang, Feiyu; Zhang, YingJia; Li, Jianzhong; Huang, Zuohua
Graphical abstract: Abstract: The reaction kinetics of alkenes + hydroperoxyl (HȮ2 ) system is of importance to low/intermediate temperature chemistry of alkanes. This work is a follow up of our previous study on 3-hexene + ȮH [1 ], . The rate coefficients were determined using the canonical variational transition-state theory. Results revealed that the asymmetric geometry of the HȮ2 radical generated numerous reaction sub-channels. The rate coefficients, with a conservative uncertainty (factor of 5), were obtained to develop the detailed chemical mechanism of 3-hexene. Additionally, potential energy surface, minimum reaction path, adiabatic ground-state energy, and activation free Gibbs energy change (ΔG) calculations were also performed.